A PSYCHOTICISM SCALE IN HINDI : I. CONSTRUCTION AND INITIAL TRYOUTS - Arora, Manju (Medknow Publications, 1980)
A psychoticism questionnaire was designed constituting 110 questions framed on the basis of the following constructs: desocialization, paranoia, thought disorder, depression, perceptual disturbance, superstitions and mania. In the initial tryout, it was administered to 40 psychotics, 40 neurotics and 40 normals and 40 items inadequately discriminating between psychotics and normals/neurotics were deleted. The revised questionnaire was administered, in second tryout, to 50 psychotics, 50 neurotics and 50 normals. The results were again subjected to item analysis and 10 more items were deleted as they could not discriminate significantly between neurotics and psychotics or where they discriminated between normals and neurotics. Kuder-Richardson formula 20 was used for reliability and criterion validity was assessed by comparing the three diagnositic groups with one another. Both these were satisfactory. Thus a psychoticism questionnaire of 60 items was constructed.